Distortion analyses of combined adhesive-riveted lap joints - Fongsamootr T. (2014)
High and low modulus adhesives have been widely used to bond metallic-to-metallic and metallic-to-composite structures. Low modulus adhesive layers (such as sealants) are used to restrict the entry of moisture and retard corrosion. High modulus adhesives (such as epoxies), are used to mainly to bond the parts. Unfortunately, the mechanical effects of thin epoxy adhesive layers on the distortion of riveted lap joints have resisted analysis and remain ill defined. In this research, finite element analyses (FEA) and the TALA method were used to analyze riveted lap joint behavior with variations in rivet spacing and the stiffness of the adhesives. The FEA results are compared with experimental results to validate the computer models. The results show that the maximum tensile stress increases with increases in rivet spacing and decreases with adhesive stiffness. Thus, the SCFs increase when the rivet spacing is increased and when the adhesive stiffness is decreased. The agreement between the SCF-values derived from the experiments and those obtained from the finite element analyses provide a measure of experimental validation for the finite element and TALA analyses. © 2004 - IOS Press and the authors. All rights reserved.